Aneurysmal and haemangiopericytoma-like fibrous histiocytoma. Issue 4 (April 1996) - Zelger, B W; Zelger, B G; Steiner, H; Ofner, D
Abstract : AIM: To describe the clinicopathological features of 33 aneurysmal fibrous histiocytomas (AFH), including five cases with a haemangiopericytoma-like pattern. METHODS: Thirty three cases of AFH were studied by using routine histology and immunohistochemistry for factor XIIIa, the "cell activity marker" E9 (anti-metallothionein), NK1C3 (CD57), smooth muscle actin (SMA), factor VIII, ulex europaeus agglutinin, JC70A (CD31), and QBEND10 (CD34). The time dependent variation in histopathological features was evaluated by statistical methods (Pearson chi 2, likelihood ratio chi 2). RESULTS: Of the AFHs, 29 of 33 occurred on the extremities of adults (age range 30 to 50 years), six of which were associated with rapid growth, probably caused by trauma, and pain. Twenty one lesions were thought to be vascular and/or melanocytic lesions, including two melanomas, because of a bluish-black and/or cystic appearance. Histologically, large areas of haemorrhage, up to 50% of the tumour bulk, lacking an endothelial lining were seen in otherwise typical fibrous histiocytomas. Five cases resembled nodular stages of Kaposi's sarcoma. Variable haemosiderin deposition in histiocytes (18/33) and giant cells (11/33) was suggestive of haemosiderotic histiocytoma. A haemangiopericytoma-like pattern was seen in five otherwise indistinguishable cases. On immunohistochemistry, variable reactivity was seen for factor XIIIa (18/30), with E9 (18/30), NK1C3 (19/30), and for SMA (14/30), but labelling for vascular markers was not detected. Early lesions without iron deposition were factor XIIIa positive; late lesions with iron deposition were factor XIIIa negative. Labelling for SMA correlated with prominent sclerosis. CONCLUSION: AFHs, including a haemangiopericytoma-like variant, have a characteristic time dependent histological and immunophenotypic profile, clearly different from nodular type Kaposi's sarcoma.